Fatal diquat intoxication - Jović-Stošić Jasmina; Babić Gordana; Todorović Veljko (Vojnosanitetski Pregled)
Background. Since the introduction of diquat in agriculture practice in 1960's, about 40 cases of poisoning have been described in detail in medical literature. Case report. We presented two cases. A case one, a 35-year-old, previously healthy, woman ingested 14% diquat solution. The poisoning had fulminant course, consisted of severe stomachache, vomiting, cardiocirculatory shock, respiratory failure and cardiac arrest 20 hours post-ingestion. Autopsy revealed myocardial infarction, bronchopneumonia and incipient renal damage. A case two, a 64-year-old man developed severe gastroenteritis, corrosive lesions of mucosal surfaces, acute renal injury, arrhythmias, brain stem infarction and bronchopneumonia. The diagnosis of diquat poisoning was made retrospectively upon the clinical picture and identification of pesticides he had been exposed to. The patient died 18 days post-exposure. The most prominent findings on autopsy were pontine hemorrhage and infarction, bronchopneumonia, left ventricle papillary muscle infarction and renal tubular damage. Conclusion. Cardiocirculatory disturbances led to fatal complications, the heart and brain infarction. We pointed out the heart as one of the most severely affected organs in diquat poisoning.